Annurca peel extract: from the chemical composition, through the functional activity, to the formulation and characterisation of a topical oil-in-water emulsion. Issue 12 (17th June 2016) - Sansone, Francesca; Esposito, Tiziana; Mencherini, Teresa; Piccinelli, Anna Lisa; Gazzerro, Patrizia; Picerno, Patrizia; Russo, Paola; Del Gaudio, Pasquale; Essolito, Massimilano; Campiglia, Pietro; Aquino, Rita P.
Abstract : The aim of this study was to produce a hydro-alcoholic safe antioxidant Malus pumila Miller cv Annurca peel extract (APE) useful as functional ingredient in an oil-in-water emulsion. Results showed that APE contains a hydroxycinnamic acid (chlorogenic acid), flavonol glycosides (quercetin derivatives) and a dihydrochalcone, phloridzin (phloretin-2- O -glucoside). The isoquercitrin (quercetin-3- O -glucoside) content was quantified in 0.3% w/w of extract. APE showed a significant and concentration-dependent free-radical scavenging activity correlated to its polyphenols content. No cytotoxic effect was observed in primary human epidermal keratinocyte adults and dermal fibroblast cell lines. The formulative approach led to produce a stable emulsion able to load a high amount of APE, up to 6.0% w/w. The homogenous distribution of APE in the emulsion was clearly demonstrated by fluorescence microscopy analysis. The emulsion resulted able to enhance the in vitro release rate of APE through synthetic membranes with respect to the raw material. Abstract :